Pengaruh Inflasi dan Pertumbuhan Ekonomi Terhadap Laba Bank Umum yang Terdaftar Di BEI - Effendy Sutejo (Universitas Tarumanagara, 2019)
The aim of this research was to analyze the influence of inflation and gross domestic product (GDP) growth against net interest margin (NIM). Population of this research is all commercial banks listed in Indonesia Stock Exchange (IDX) from 2015 to 2017. Samples collected by purposive sampling method. After passed the purposive sampling phase, 32 commercial banks have been selected as samples, which then categorized into 2 groups, small cap banks and big cap banks. The test results showed that inflation does not have significant effect on NIM of small cap banks. On the other hand, inflation has a significant and negative effect on NIM of big cap banks. The test results also showed that GDP growth does not have significant effect on neither small cap banks nor big cap banks.